REFORMATION OF POLITICAL SYSTEM OF UKRAINE: CHALLENGE OF THE PRESENT - Савченко, І.Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article urgent problem of reform of political system is considered. Optimization ways of functioning and cooperation of supreme bodies of state power under circumstances of parliamentary-presidential form of government are suggested. Necessity of reach a consensus between branches of government in order to avoid current contradictions and discrepancies is marked.